2010
DOI: 10.1097/bot.0b013e3181efa8fe
|View full text |Cite
|
Sign up to set email alerts
|

The Effect of Bone Morphogenetic Protein-2, Bone Morphogenetic Protein-7, Parathyroid Hormone, and Platelet-Derived Growth Factor on the Proliferation and Osteogenic Differentiation of Mesenchymal Stem Cells Derived From Osteoporotic Bone

Abstract: BMP-7, BMP-2, PTH, and PDGF-BB were observed to have a positive effect on osteogenic differentiation of MSCs. BMP-7 and PDGF-BB (in high doses) could be considered most potentially advantageous because they enhance both proliferation and osteogenic differentiation of MSCs derived from elderly osteoporotic bone.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
86
0
2

Year Published

2012
2012
2019
2019

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 109 publications
(92 citation statements)
references
References 20 publications
4
86
0
2
Order By: Relevance
“…Fortunately, PDGF as a potential drug therapy has been confirmed to enhance both proliferation and osteogenic differentiation of BMSCs derived from patients with osteoporosis. 39 PDGF-BB is a potent mitogen, 40 and the present results also suggest that the immobilized rhPDGF-BB on the nanotube surface did promote the proliferation of BMSCs from OVX rats (Supplementary Figure S4). In addition, those cells exhibited higher expression of both osteoblast-related transcription factor osterix and osteoblast-related protein OCN by stimulation by the immobilized rhPDGF-BB.…”
Section: Discussionsupporting
confidence: 49%
See 1 more Smart Citation
“…Fortunately, PDGF as a potential drug therapy has been confirmed to enhance both proliferation and osteogenic differentiation of BMSCs derived from patients with osteoporosis. 39 PDGF-BB is a potent mitogen, 40 and the present results also suggest that the immobilized rhPDGF-BB on the nanotube surface did promote the proliferation of BMSCs from OVX rats (Supplementary Figure S4). In addition, those cells exhibited higher expression of both osteoblast-related transcription factor osterix and osteoblast-related protein OCN by stimulation by the immobilized rhPDGF-BB.…”
Section: Discussionsupporting
confidence: 49%
“…37,38 However, recent data suggest that BMSCs derived from patients with osteoporosis have a lower growth rate and osteogenic potential. 39 We tested the osteogenic differentiation ability of the BMSCs from the OVX rats. Their ALP activity and calcium deposition capacity were inferior to that of cells from the sham rats (Supplementary Figure S3).…”
Section: Discussionmentioning
confidence: 99%
“…Similarly, Pountos et al observed an enhancement of proliferation and osteogenic differentiation due to BMP-2 and BMP-7 in hMSC derived from osteoporotic bone [30]. With regard to the BMP signal transduction, our group recently showed a reduced phosphorylation of ERK1/2, but an accurate activation of SMAD1/5/8 [7].…”
Section: Discussionmentioning
confidence: 89%
“…Cell isolation and culture expansion was performed according to previously described methods [22][23][24][25] . Nucleated cells were isolated from the cancellous bone of the greater trochanter of fresh porcine bone obtained from the local abattoir on the day of sampling.…”
Section: Cell Isolation Cultivation and Expansionmentioning
confidence: 99%